Web-Based Information System for the Language Unit at Politeknik Penerbangan Surabaya - Lady Silk Moonlight; Maulana Anifa Silvia; Anton Budiarto; Faoyan Agus Furyanto; Ahmad Musadek; Lusiana Dewi Kusumayati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to develop a web-based information system for the Language Unit of Politeknik Penerbangan Surabaya to replace the existing manual management processes. The system is designed to improve the efficiency of information delivery, registration, and payment for services such as language training, English proficiency tests, and document translation. The development process adopts the Agile methodology, which enables iterative development and rapid adaptation to user needs. The system implementation utilizes WordPress as the content management system and MySQL as the primary database to ensure data reliability and ease of management. The results show that the developed website provides faster, more flexible, and secure access for users. Furthermore, the system supports a mobile-friendly design, allowing users to access information anytime and anywhere. Thus, the system successfully supports the modernization of language services through efficient and sustainable digitalization.